2010
DOI: 10.4269/ajtmh.2010.09-0165
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Malaria and Intestinal Helminth Coinfection on Birth Outcomes in Kumasi, Ghana

Abstract: Abstract. This study was conducted to investigate the effect of Plasmodium falciparum and intestinal helminth coinfection on maternal anemia and birth outcomes. A cross-sectional study of 746 women who delivered in two hospitals in Kumasi was conducted. Data were collected using an investigator-administered questionnaire and from patients' medical records. Blood was collected for determination of P. falciparum and hemoglobin levels. Adverse pregnancy outcomes were high (44.6%). Coinfection (versus no infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 36 publications
4
48
1
Order By: Relevance
“…[13][14][15] These data are consistent with those of recent studies in sub-Saharan Africa. 5,6 Another important outcome to draw from this data is the high percentage of infants born with LBW and a low WZS.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…[13][14][15] These data are consistent with those of recent studies in sub-Saharan Africa. 5,6 Another important outcome to draw from this data is the high percentage of infants born with LBW and a low WZS.…”
Section: Discussionsupporting
confidence: 83%
“…And in those women with anemia, co-infection was associated with an increased risk of LBW, preterm delivery, and small size for gestational age, which was not completely explained by the presence of malaria infection. 13 Another study in Nigeria showed a high prevalence of malaria infected pregnant women who were co-infected with helminths (45%) and suggested a trend towards lower maternal hemoglobin levels in those co-infected. 14 Apart from maternal anemia and other measures of perinatal health such as birthweight, prematurity, and stillbirths, there are other potential morbidities from helminth infection and polyparasitism on fetuses that warrant attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that placental malaria at delivery was associated with an increased risk of LBW and PTD [29]. This led us to hypothesize that parasite derived factors and host factors such as heme and heme oxygenase-1 play a role in the pathogenesis of malaria.…”
Section: Discussionmentioning
confidence: 97%
“…51 By contrast, others have reported varying increases in the risk of anemia with malaria and helminth coinfection across various age groups. 46,[52][53][54][55][56] Given that there are more than 400 million cases of P. falciparum each year, 57 many occurring in areas endemic for helminths, a greater understanding of the interaction between these two highly prevalent and clinically important parasitic diseases could lead to the formulation of more effective control strategies for both.…”
Section: Discussionmentioning
confidence: 99%